2010
DOI: 10.1128/jvi.02438-09
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Specific CD8+T-Cell Responses Better Define HIV Disease Progression than HLA Genotype

Abstract: ؉ T-cell counts (4 to 8 times longer), while responses to variable epitopes presented by B35 alleles (DL9 and IL9) resulted in more rapid progression. The plasma viral load was higher in B57/58 ؉ and B27 ؉ subjects lacking the conserved B57/58-and B27-restricted responses. The presence of certain B57/58-, B27-, and B35-restricted HIV-specific CD8 ؉ T-cell responses after primary HIV-1 infection better defined disease progression than the HLA genotype alone, suggesting that it is the HIV-specific CD8 ؉ T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
58
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 35 publications
3
58
1
Order By: Relevance
“…Even so, large cross-sectional studies have found that subjects whose CD8 + T cells preferentially target the structural protein Gag are more likely to sustain lower VL in chronic HIV-1 infection (9). The importance of epitope specificity to virus control is also suggested by genetic studies that found lower VL and delayed disease progression associated with the expression of certain HLA alleles, B*57/5801, B*27, B*51, and B*8101 (10)(11)(12), and the finding that protection is linked to the number of T cell responses restricted by these HLA types (13).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Even so, large cross-sectional studies have found that subjects whose CD8 + T cells preferentially target the structural protein Gag are more likely to sustain lower VL in chronic HIV-1 infection (9). The importance of epitope specificity to virus control is also suggested by genetic studies that found lower VL and delayed disease progression associated with the expression of certain HLA alleles, B*57/5801, B*27, B*51, and B*8101 (10)(11)(12), and the finding that protection is linked to the number of T cell responses restricted by these HLA types (13).…”
Section: Introductionmentioning
confidence: 78%
“…13,24). This is the first study to our knowledge to comprehensively measure and analyze vertical immunodominant T cell hierarchies in HIV-1 infection and to relate these to measurements of longitudinal immune escape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further characterization of the differences between HLA-B*57/B*5801-positive individuals to distinguish TW10 responders from nonresponders may unravel the mechanisms behind effective control of viremia. A recent study by Dinges et al reported that HLA-B*57/B*58:01 individuals who lacked responses to the conserved epitopes had higher plasma viral loads (10), suggesting that it is the precise genomic region targeted rather than the allele per se that is predictive of disease progression. Here we show that specific targeting of the highly conserved TW10 epitope in B*58:01-positive individuals contributes to this association.…”
Section: Discussionmentioning
confidence: 99%
“…It now is clear that both CTL and NAb responses against HIV can be directed to particular epitopes that are more effective in controlling viremia than those targeting alternate epitopes (8,9). Similarly, ADCC responses to specific epitopes may be more effective in controlling HIV replication than others.…”
mentioning
confidence: 99%